Live Weight Estimation by Chest Girth, Body Length and Body Volume Formula in Minahasa Local Horse - B J Takaendengan; U Paputungan; R R Noor; S Adiani (Media Peternakan, 2012)
Study was conducted in the regency of Minahasa to estimate horse live weight using its chest girth, body length and body volume formula (cylinder volume formula) represented by animal chest girth and body length dimensions, particularly focused in Minahasa local horses. Data on animal live weight (LW), body length (BL), chest girth (CG) and body volume were collected from 221 stallions kept by traditional household farmers. Animal body volume was calculated using cylinder volume formula with CG and BL as the components of its formula. Regression analysis was carried out for LW with all the linear body measurements. The data were classified on the basis of age. Age significantly (P < 0.05) influenced the body measurements except animal body length (P>0.05). Animal live weight was predicted by simple regression models using dependent variable (Y) of the animal live weight and independent variable (X) of the animal body measurement, either body length, chest girth, or body volume. The correlations between all pairs of measurements were highly significant (P < 0.01) for all age groups. Regression analysis showed that live weight could be predicted accurately from body volume (R2= 0.92) and chest girth (R2= 0.90). Simple regression model that can be recommended to predict horse live weight based on body volume with their age groups ranging from 3 to ≥10 years old was as follow: Live weight (kg)= 5.044 + 1.87088 body volume (liters). The analyses of data on horse chest girth, body length and body volume formula provided quantitative measure of body size and shape that were desirable, as they enable genetic parameters for these traits to be estimated and also included in breeding programs.